1962
DOI: 10.1099/00221287-28-4-641
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Computer Taxonomy

Abstract: StrMMARYThe systematic relationships among 54 strains of bacteria, representing principally the genera Achromobacter, Aerobacter, Alcaligenes, Eschmichia, Mima, Pseudomonas, Serratia and Streptococcus, were examined by computer methods. Seventy-one properties of these organisms were determined, and the resulting data scored in different ways (according to various proposed techniques) before being submitted to an appropriate computer program for calculation of similarity (S) values. These comparative studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
4
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…Serratia and Shigella seem to form distinct generic groups (3b and 3c). A similarly distinct Serratia subgroup was reported by Beers et al (1962). Although some studies (e.g., Beers et al, 1962;Lockhart and Hartman, 1963) have indicated a separation between strains of Escherichia and Enterobacter, these two genera seem in this study to combine with Erwinia and Salmonella into a single, rather diffuse cluster (group 3a) within the enterobacteria.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Serratia and Shigella seem to form distinct generic groups (3b and 3c). A similarly distinct Serratia subgroup was reported by Beers et al (1962). Although some studies (e.g., Beers et al, 1962;Lockhart and Hartman, 1963) have indicated a separation between strains of Escherichia and Enterobacter, these two genera seem in this study to combine with Erwinia and Salmonella into a single, rather diffuse cluster (group 3a) within the enterobacteria.…”
supporting
confidence: 70%
“…A similarly distinct Serratia subgroup was reported by Beers et al (1962). Although some studies (e.g., Beers et al, 1962;Lockhart and Hartman, 1963) have indicated a separation between strains of Escherichia and Enterobacter, these two genera seem in this study to combine with Erwinia and Salmonella into a single, rather diffuse cluster (group 3a) within the enterobacteria. Erwinia amylovora, the type species of its genus, bears little similarity to other enterobacteria, an observation confirmed with several strains of E. amylovora during a more detailed study of the genus Erwinia (Koenig and Lockhart, unpublished data).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…As presented in Table 2, 70 characters of a bacterial strain were examined, and the resulting 143 features scored were analyzed in a computer NEAC 2230 (Nippon Electric Co.). All methods to determine the characters as well as similarity values (S value) between two strains were previously described by Nakamura and Nishida [15,16] ; data were coded following the procedure III described by Beers et al [2] and sorted by the single linkage method of Sneath [21]. To study spore formation, bacteria from the liver infusion broth were grown on BHI agar for 2 days at 37 C under an anaerobic condition.…”
Section: Methodsmentioning
confidence: 99%
“…Since the application of computer analysis of taxonomic data for the bacteria was first proposed by Sneath (28), many investigators have made use of Adansonian principles to describe and classify bacteria. Various authors have examined the techniques and have proposed modifications of the methods for Adansonian classification (1, 2,27,30). Adansonian principles were first applied to marine microorganisms by Colwell and Liston '(5), and other investigators have since similarly studied the marine bacteria (9,11,21).…”
mentioning
confidence: 99%